Ixekizumab‐induced urticarial drug eruption - Ayaka Kaneoka; Natsuko Saito‐Sasaki; Etsuko Okada; Yu Sawada (Wiley, 2023)
Abstract Biological agents targeting inflammatory skin diseases have dramatically overcome many of the limitations of older oral therapeutic options. Among the various biological agents, ixekizumab is a humanised monoclonal antibody that blocks the biological activity of IL‐17A, which exhibited high efficacy against psoriasis. Although there are a limited number of cutaneous adverse reactions, biologic‐induced type I allergic reactions are rare. Herein, we report a case of ixekizumab‐induced urticaria.